2005
DOI: 10.1111/j.1553-2712.2005.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Online Medical Command Communication and Emergency Medical Services Documentation of Informed Refusals

Abstract: Paramedic and OLMC physician communication for patients refusing out-of-hospital medical treatment and/or transport is inadequate in the Cleveland EMS system. A written nontransport worksheet improves documentation of the refusal encounter but does not ensure that every patient who refuses possesses medical decision-making capacity and the capacity to provide an informed refusal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Non-conveyance rates for general patient populations ranged from 3.7% up to 93.7% [28, 30, 31, 3335, 37, 38, 4043, 45, 46, 49, 51, 52, 57, 60, 61, 64, 68, 77, 81]. Seventeen studies reported non-conveyance rates for specific patient populations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Non-conveyance rates for general patient populations ranged from 3.7% up to 93.7% [28, 30, 31, 3335, 37, 38, 4043, 45, 46, 49, 51, 52, 57, 60, 61, 64, 68, 77, 81]. Seventeen studies reported non-conveyance rates for specific patient populations.…”
Section: Resultsmentioning
confidence: 99%
“…Criteria to guide the (non-) conveyance decision described mostly are abnormal vital functions related to ‘breathing’ (respiration rate, respiratory distress, dyspnea), abnormal vital functions related to ‘circulation’ (systolic/diastolic blood pressure, pulse), suspected or confirmed ingestion of alcohol or drugs, and an altered level of consciousness (Glasgow coma scale) [28, 29, 39, 40, 43, 46, 5154, 59, 70, 72, 73, 75, 79, 84, 88]. Ten of these studies described more specific flowcharts, tools, checklist or standard operating procedures for non-conveyance in general [43, 51, 72], patients who refuse conveyance [29, 40, 46], and patients who had fallen [84], with supraventricular tachycardia [39], with social problems [28], with hypoglycaemia [53], and post-ictal patients [53].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations